Detection of foreign bodies in canned foods using ultrasonic testing - Hrairi, Meftah; Elias, Mohd Azimin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Foreign bodies in packaged foods may pose both a safety risk and a risk of perceived degradation of quality. When food products are manufactured or packaged, small foreign objects might end up in the product. It is naturally desirable for the food industry that all foreign bodies are detected and removed before they reach customers. In this study, the ultrasonic method was used to detect the foreign bodies in canned foods. In order to establish a technical concept for the detection of foreign bodies in canned foods, an experimental investigation was carried out using pulse-echo ultrasonic testing. A number of simulated foreign object pieces were deliberately put inside the canned food and the results were analyzed. The approach demonstrates that ultrasound has potential for application in many industrial food packaging environments where foreign objects need to be detected. Indeed, detection up to 4 millimeter foreign body size has been done for rock and metal foreign bodies.